The Effect of Time Token Learning Model on Students' Interest in Learning Mathematics - Hanum, Farida; Elfrianto, Elfrianto (EduMatika: Jurnal MIPA, 2022)
This study aims to determine whether there is an effect of the time token learning model on the students' interest in learning mathematics at SMP Muhammadiyah 7 Medan in the 2022/2023 academic year. The population of this study were all students of SMP Muhammadiyah 7 Medan, totaling 142 students. While the samples used in this study were students of SMP Muhammadiyah 7 Medan class VIII-1, amounting to 34 students. This research uses quantitative research with a one-group pretest-posttest design. The data analysis technique used in this study is the normality test using the Kolmogorov Smirnov test and hypothesis testing using the t test. the tested data will be processed using the SPSS program.  The results of this study indicate that there is an effect of the time token learning model on students' interest in learning mathematics at SMP Muhammadiyah 7 Medan class VIII-1. This can be seen from the results of hypothesis testing using t-test with tcount > ttable at level =0.05, namely 9.595> 2.034. It can be concluded that Ho is rejected and Ha is accepted